Método para controle da qualidade de medicamentos sólidos por difração de raios X - Salvi, Simone Toledo Bonemer de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The x-ray powder diffraction (XPPD) is an excellent technique to obtain information about the crystal solid state on active pharmaceuticals ingredients (active ingredient) and inactive (excipients). Knowing that these ingredients can exhibit the phenomenon of polymorphism, this technique is efficient to differentiate among polymorphic forms. Beyond the problem of polymorphism, also, can occur changes in the crystallinity, dimensions and crystallites forms (physical characteristics), that must be maintained as the same characteristics that were used during the development and registration of medicament, because this factors can affect the farmaco bioavailability. To adequate analysis of these solids ingredients, some methods using DRXP data are recommended: Rietveld method (RM), Le Bail method (MLB), Pawley Method (PM) and the PONKCS method (Partial Or No Known Crystal Structure) which is based on RM. The RM can be adequately applied on characterization and quantification of crystal forms in polycrystalline materials, although the crystalline structure is necessary in this method. However, for many of these ingredients, there are few crystallographic information about, and for the cases that the crystal structure are unknown or partially known, the PONKCS method can be applied. As showed in the case of the excipient α-lactose monohydrate, present in the antihypertensive hydrochlorothiazide, and quantified 70.03wt% of lactose and 29.97wt% of hydrochlorothiazide, and in the case of the magnesium stearate, quantified in 1.4wt% on atenolol tablet. The PONKCS and Le Bail methods are used for profile fitting, and for identification of peaks in partially known crystal phases, but not used for quantification. The LBM and PM were used for profile fitting in the cases that the PONKCS method were applied, and in atenolol tests. The present work aimed identify and characterize excipients and pharmacos...

A técnica de difração de raios X por policristais (DRXP) é excelente para obter informações sobre o estado sólido cristalino em insumos farmacêuticos ativos (princípios ativos) e inativos (excipientes). Tendo em vista que estes insumos podem apresentar o fenômeno do polimorfismo, esta técnica é eficiente para a diferenciação entre as diferentes formas polimórficas. Além do problema de polimorfismo, também podem ocorrer mudanças na cristalinidade, dimensões e forma dos cristalitos (características físicas), as quais devem ser mantidas com as mesmas características das que foram usadas durante o desenvolvimento e registro do medicamento, pois esses fatores podem alterar a biodisponibilidade do fármaco. Para a análise adequada destes insumos sólidos, alguns métodos fazendo uso dos dados de DRXP são recomendados: o método de Rietveld (MR), método de Le Bail (MLB), método de Pawley (MP) e o método de PONKCS (Partial Or No Known Crystal Structure) que é baseado no MR. O MR pode ser adequadamente aplicado na caracterização e quantificação das formas cristalinas presentes em materiais policristalinos, embora ele seja limitado aos casos onde a estrutura cristalina seja conhecida. Porém, para muitos insumos a literatura ainda dispõe de pouca informação cristalográfica e para os casos em que a estrutura cristalina não seja conhecida ou seja parcialmente conhecida, o método PONKCS pode ser aplicado, conforme mostrado no caso do excipiente lactose monoidratada presente no anti-hipertensivo hidroclorotiazida, tendo sido encontrado de 70,0% lactose e 29,9% de hidroclorotiazida e do estearato de magnésio, presente em 1,4% em massa no comprimido de atenolol. Os métodos de Le Bail e de Pawley são utilizados para a decomposição do padrão e para identificação dos picos em fases com estruturas parcialmente conhecidas, porém não podem ser utilizados para a quantificação...
Keywords: Raios X; Cristalografia; Polimorfismo (Cristalografia); Fármacos; Crystallography